Association between intrinsic capacity, changes in intrinsic capacity, and cardiometabolic multimorbidity: results from three prospective cohort studies - Wang, Ziyue; Wang, Lu; Tang, Lulu; Li, Xiaorui; Lu, Yu; Yu, Xiaoli; Liu, Fei; Zhu, Xiaoping (Frontiers in Endocrinology, 2025)
BackgroundIntrinsic capacity (IC)is closely associated with cardiometabolic health in middle-aged and older adults. The purpose of this study was to determine the associations of baseline IC, cumulative IC scores, and their dynamic changes with the risk of incident cardiometabolic multimorbidity (CMM).MethodsUsing data from three prospective cohorts, the China Health and Retirement Longitudinal Study (CHARLS), the English Longitudinal Study of Ageing (ELSA), and the Health and Retirement Study (HRS), participants who met the eligibility criteria were included in this study. Kaplan-Meier curves and Cox models analyzed risk trends and associations.ResultsA total of 11,916 participants were included based on the inclusion and exclusion criteria. At baseline, the risk of CMM in the injured group was significantly higher than that in the non-injured group(Pooled: HR = 1.40, 95% CI 1.30-1.52, P < 0.001); Cumulative IC scores showed a graded association with CMM risk: individuals with moderately reduced scores (≈1 SD below intact) had higher risk (HR = 1.22, 95% CI 1.09–1.36), and those with substantially reduced scores (>1 SD below intact) had even higher risk (HR = 1.61, 95% CI 1.47–1.78). For dynamic changes, CMM risk was significantly higher in persistent impairment and decline groups; even the improvement group had higher risk than the no-decline group (Decline: HR = 1.25, 95% CI 1.10-1.42, P < 0.001; Improvement: HR = 1.28, 95% CI 1.13-1.45, P < 0.001; Persistent impairment: HR = 1.63, 95% CI 1.48-1.80, P < 0.001).ConclusionsIC and its changes relate to CMM risk. Even with IC improvement, risk remains higher than in those with intact IC. Precise strategies to delay IC decline and individualized interventions are needed for CMM control.